The Routledge Handbook of Festivals. - Mair, Judith, ....- (London : New York : Routledge & K. Paul; Humanities P., 2022)
This handbook offers a comprehensive evaluation of the most current research, debates and controversies surrounding festivals. It is divided into nine sections that cover a wide range of theories, concepts and contexts, such as sustainability, festival marketing and management, the strategic use of festivals and their future. Featuring a variety of disciplinary, cultural and national perspectives from an international team of authors, this book will be an invaluable resource for students and researchers of event management and will be of interest to scholars in the fields of anthropology, sociology, geography, marketing, management, psychology and economics.
Keywords: Event management